Development and evaluation of the Preparedness Guideline to promote Adaptability of Professional Nurses who Provide Care for the Patient under Investigation and Confirmed Cases of COVID-19 - Vimonvattana, Ampan; Vongareesawat, Chantrarat (Vajira Nursing Journal, 2024)
This study aimed to develop and evaluate the preparedness guideline to promote adaptability of professional nurses who provide care for the patient under investigation and confirmed cases of COVID-19. The sample was composed of registered nurses at Vajira Hospital who met inclusion criteria and were divided into two phases. Phase 1, the 342 nurses were participated in the developing preparedness guideline. Phase 2, the 44 nurses who provided cares for the patient under investigation and confirmed cases of COVID-19 and deployed the preparedness guideline in their works. The research instruments included the preparedness guideline in providing cares for the patient under investigation and confirmed cases of COVID-19, a focus group discussion form approved by the experts, a feasibility assessment form of the preparedness guideline to promote adaptability of professional nurses who provide care for the patient under investigation and confirmed cases of COVID-19, and the adaptability questionnaire. The result of implementing the preparedness guideline to promote adaptability of professional nurses who provide care for the patient under investigation and confirmed cases of COVID-19 revealed that 1) most of the samples are at a practitioner level; 2) the preparedness guideline included 5 dimensions: policy, personnel, knowledge and competence of personnel, medical services, workplace atmosphere and supporting vital facilities; 3) the possibility of using the preparedness guideline was high level; and 4) all professional nurses who provided care for the patient under investigation and confirmed cases of COVID-19 had the overall mean scores of the adaptability questionnaire at high level (Mean= 3.71, SD.=0.43). The result implied that the nurses who employed the preparedness guideline can increase their adaptability for providing care the patient under investigation and confirmed cases of COVID-19 at high level.